Evaluation of Porcine Collagen Membranes Used with Guided Bone Regeneration for Critical Defects: A Histological, Histomorphometric, Immunohistochemical, and Inflammatory Profile Analysis - Ramos, Edith Umasi; Leandro, Miguel Nino Chávez; Criales, Jesús Omar Cárdenas; Buitron, Marisol Rossana Ortega; Verástegui, Edgar Simón; Carbajal, Wilbert Manzanedo; Adrianzén, Ronald Christian Solís; Grijalva, Anibal Eleuterio Espinoza; Baylon, Antonio Alberto Ballarte; Bassi, Ana Paula Farnezi (European Journal of Dentistry, 2024)
Objective The objective of this study was to compare the effectiveness of two porcine collagen membranes of different origin used for guided bone regeneration procedures.Materials and Methods Resorbable collagen membrane from porcine dermis (Bio-Gide, Geistlich Pharma AG, Wolhusen, Switzerland) and resorbable collagen membrane from porcine pericardium (Jason, Institut Straumann AG, Peter Merian-Weg, Switzerland) were evaluated; histological, histometric, immunohistochemical, and inflammatory profile analyses were performed. The study was carried out on critical defects created in the calvaria of 72 rats (Rattus norvegicus albinus, Wistar variety) divided into three groups: coagulum group (Co), porcine pericardium group (JS), and porcine collagen group (BG). The defects were filled with clot, over which the membranes were placed. The animals were euthanized 7, 15, 30, and 60 days after surgery.Statistical Analysis The Shapiro–Wilk test was used to assess data distribution. Analysis of variance (ANOVA) and the Bonferroni multiple comparison test were used to compare the differences across the mean values of the variables. Nonparametric tests, Mann–Whitney and Wilcoxon W, were used for the quantitative analysis of the inflammatory profile. A significance level of 5% (p < 0.05) was adopted with a confidence interval of 95%. SPSS software version 2.0 was used.Results A total of 1,008 analyses were performed on 288 histological slides. It was noted that both types of collagen membranes used in this study were effective for the guided bone regeneration procedure, with a greater proportion and thickness of bone formation among recipients of the BG (735 points, p = 0.021). This membrane also had greater permeability (62.25). The animals in the JS group, which received the porcine pericardial membrane, showed early and accelerated bone formation from early bone tissue, milder osteopontin and osteocalcin levels, and greater inflammatory reaction (86.4).Conclusion The collagen membrane from porcine dermis demonstrated a more orderly and physiological repair process, while the porcine pericardial membrane presented a more accelerated repair process that did not remain constant over time.
Keywords: bone regeneration; guided tissue regeneration; collagen; inflammation